Laser vs. Conventional Surgical Treatment of Hemorrhoids AComparative Study of Outcomes and Complications - Ahmad Raza Jawaid Mughal, Bahadur Khan, Abid Raza, Muhammad Idrees Achakzai, Muhammad Azhar Qureshi, Inayat Husain Anjum, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A new randomized controlled experimental comparison between laser and conventional excisionalhemorrhoidectomy demonstrates improved outcomes and reduced complications. The objective ofthe study was to evaluate operative time, postoperative pain scores, wound healing time,complication rates, and recurrence between laser hemorrhoidectomy and conventional excisional technique. A total of 1 20 adult patients